CHINA’S CENTRAL BANK AND MONETARY POLICY IN THE CONTEXT OF GLOBAL FINANCIAL CRISIS: A HISTORICAL VIEW - Wei, Shen (Bank Indonesia, 2022)
Central banks have been said to take partial responsibility for the global financial crisis. In a broader sense, central banks play a key role in shaping monetary and economic policies. After the global financial crisis, central banks are burdened with more tasks of ensuring economic growth, employment, and financial stability. This article takes a historical view towards the policy landscape and monetary instruments the People’s Bank of China, China’s central bank, has been working on to achieve various policy initiative. Although the general consensus is that China’s central bank may have more authority in policymaking, its multiple tasks, functions, and goals may constrain its capabilities and autonomy. China central bank’s ambition to internationalize Renminbi may further complicate its policy agenda and the way it deploys monetary instruments.